Optical Coherence Tomography Angiography in Retinal Vein Occlusion Treated with Dexamethasone Implant: A New Test for Follow-Up Evaluation. Issue 5 (September 2016) - Glacet-Bernard, Agnes; Sellam, Alexandre; Coscas, Florence; Coscas, Gabriel; Souied, Eric H.
Purpose: To quantitatively and qualitatively analyze patients with macular edema secondary to retinal vein occlusion (RVO) and treated with the intravitreal dexamethasone implant using optical coherence tomography angiography (OCTA). Methods: The files of patients treated with intravitreal injection of dexamethasone implant for macular edema secondary to RVO were retrospectively analyzed. Before and after injection, the following data were recorded: best-corrected visual acuity (BCVA), central macular thickness (CMT) measured using spectral-domain optical coherence tomography, fluorescein angiography, and OCTA (Optovue, Inc., Fremont, CA, USA). Results of automatic measurement of vascular density of the superficial capillary plexus (SCP) and deep capillary plexus were obtained before and after treatment and compared to those of healthy subjects matched for age and sex. Results: Seven eyes of 7 patients (mean age, 76 years; 57% male) were analyzed, including 3 cases of central RVO and 4 cases of branch RVO. All patients received 1 intravitreal injection of dexamethasone implant. After a mean follow-up of 2 months, CMT significantly decreased from 657 µm to 324 µm on average and BCVA increased from 20/100 to 20/50 (p = 0.017 and p<0.001, respectively). At the SCP, the mean whole en face vascular density slightly decreased during follow-up from 43.21% to 42.76% (not statistically significant). Vascular densities were largely inferior to those observed in control subjects (p≤0.01 in all quadrants). Conclusions: This study confirms the potential contribution of OCTA as a novel noninvasive imaging technology that enables a quantitative and qualitative evaluation of the follow-up of macular edema in RVO. Optical coherence tomography angiography may complement advantageously multimodal imaging to monitor patients with RVO.